An opportunity taken: Sunshine Coast University Private Hospital’s Perioperative Nurse Surgeon’s Assistant experience - Catherine Smith; Toni Hains; Natasha Mannion (Journal of Perioperative Nursing)
The Ramsay Health Care facility, Sunshine Coast University Private Hospital (SCUPH), opened on the 4th of November 2013. The facility has six operating theatres offering surgical services in orthopaedics; ear, nose and throat; general; urology; gynaecology and gastroenterology. The private hospital will be co-located on the site of the pending public hospital, Sunshine Coast University Hospital, on the Kawana Health Campus.